English additional language student teachers’ development of oral strategic competence and confidence during lectures - Meyers, Rozanne (Journal for Language Teaching, 2023)
This paper argues that when student teachers use English, their additional language as a tool of learning interaction during lectures, it influences their oral strategic and discourse competence and confidence, negatively and positively. Within the qualitative approach an interpretive framework is adopted using two data collection tools, namely drawings and unstructured interviews. Drawings illustrated how participants perceived themselves during lectures when they had to use English during oral interaction with lecturers and fellow students. Unstructured interviews were conducted after participants completed their drawings. The raw data from the two tools were analysed using a thematic approach. The analysis found that collaborating with fellow students in making meaning of oral communication during lectures, increased students’ oral competence and their confidence because they were communicating in smaller groups. However, in certain situations, collaborating with students also decreased their confidence. Furthermore, reciprocal facial expressions and the body language of those who engaged orally with the student teachers, increased their oral confidence as it served as an indication to them that they were understood. Based on the findings, recommendations are made regarding interactions during lectures for lecturers and lecturing practice in relation to its effects on the development of oral strategic competence and confidence in student teachers.